Bending, buckling, and free vibration of magnetoelectroelastic nanobeam based on nonlocal theory. (May 2016) - Li, YS; Ma, P; Wang, W
In this work, bending, buckling, and free vibration of magnetoelectroelastic nanobeam are investigated based on nonlocal theory and Timoshenko beam theory. According to Maxwell equation and magnetoelectric boundary condition, the variation of electric and magnetic potentials along the thickness direction of the nanobeam is determined. Using Hamilton's principle, the governing equations of the magnetoelectroelastic nanobeam are derived. Numerical results reveal the effects of the nonlocal parameter and the electric and magnetic potentials on the transverse displacement, rotation, buckling load, and natural frequency. These results may be useful in the analysis and design of smart structures constructed from magnetoelectroelastic materials.